The Rise of Human Rights Limits to Migration Control – A European Perspective - Bast, Jürgen; Justus Liebig University Giessen (My University, 2024)
One crucial difference between migration and other areas is that the web of individual rights woven by human rights law has remained thin for a long time. Migration has long looked like the last bastion of sovereignty while other fields of law became subject to a rights revolution imposing meaningful constraints on public authorities. This essay confronts the legacy of immigration exceptionalism with developments in the European legal space since the 1990s. Catalyzed by the case law of the European Court of Human Rights (ECtHR), human rights eventually have taken center stage in legal and political struggles challenging the power to exclude. The expansion of human rights discourse in contemporary Europe is seen as part of a larger trend. Mutually reinforcing processes of “humanrightization” in law, politics, and everyday practice have given rise to successful claims raised by migrants and other social actors seeking to limit the governmental power of migration control. Humanrightization of migration discourse makes it possible to formulate far-reaching demands for the inclusion of migrants within the framework of the recognized rules of legal argumentation—a “positivist human rights maximalism.”
Keywords: ddc:340